2021
DOI: 10.1111/jch.14369
|View full text |Cite
|
Sign up to set email alerts
|

Live birth/parity number and the risk of incident hypertension among parous women during over 13 years of follow‐up

Abstract: The effect of live birth/parity number on incident hypertension was investigated among Iranian parous women aged 30-70 years. The study population included 2188 normotensive women who were enrolled in 1999-2001. They were followed for incident hypertension (based on JNC 7 report) by 3-year intervals up to April 2018. Multivariable Cox proportional hazard models, adjusted for a wide set of potential hypertension risk factors, reproductive factors, and pregnancy complications, were applied to estimate hazard rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
9
2
Order By: Relevance
“…These findings align with those of the study by Xu and colleagues, 14 which showed that women with a parity of 4 and ≥5 had a higher risk of hypertension than those with a parity of zero or one, and the association diminished after adjusting for BMI and waist circumference. However, our study contradicted the study by Moazzeni and colleagues, 13 which found that women with parity of 3 had a higher risk of hypertension than those with a parity of 2 even after adjusting for BMI. The average age was 43.64 years in Moazzeni's study, and differences in ethnicity, lifestyle, and study design could have led to different results from our results 13 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These findings align with those of the study by Xu and colleagues, 14 which showed that women with a parity of 4 and ≥5 had a higher risk of hypertension than those with a parity of zero or one, and the association diminished after adjusting for BMI and waist circumference. However, our study contradicted the study by Moazzeni and colleagues, 13 which found that women with parity of 3 had a higher risk of hypertension than those with a parity of 2 even after adjusting for BMI. The average age was 43.64 years in Moazzeni's study, and differences in ethnicity, lifestyle, and study design could have led to different results from our results 13 .…”
Section: Discussioncontrasting
confidence: 99%
“…The average age was 43.64 years in Moazzeni's study, and differences in ethnicity, lifestyle, and study design could have led to different results from our results. 13 On the other hand, Jang reported that parity was associated with a decreasing risk of hypertension in postmenopausal women in Korea. 11 Differences in covariates, study design, lifestyle including intake of salt in eating habits, and number of participants might produce different results from those of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the reduction of estrogen exposure will cause the disorder of lipid metabolism, hypertension, hyperglycemia, and other components of MetS (52,53), which lead to the occurrence of MetS. Second, pregnancy can cause a series of physiological function changes, including but not limited to insulin resistance, abnormal lipid metabolism, hypertension, and central obesity (54)(55)(56)(57). Insulin resistance always appears simultaneously with other metabolic-related diseases, which play a crucial role in the development of MetS (15).…”
Section: Discussionmentioning
confidence: 99%